An Update in Cystic Fibrosis-Related Diabetes in Children and Adolescents - Dana-Teodora Anton-Păduraru; Alina Mariela Murgu; Mădălina Andreea Donos; Felicia Trofin; Alice Nicoleta Azoicăi; Paula Popovici; Aurelian Bogdan Stana; Ionela Gheorghiescu; Laura Mihaela Trandafir (Children, 2023)
This paper delineates several aspects of cystic fibrosis-related diabetes (CFRD)—a common complication of cystic fibrosis (CF). CFRD exhibits a predilection for older individuals with CF, yet it also extends its influence on children and adolescents. Scientific insights postulate a potential link between CFRD and the aberrant mucus production within the pancreas, thereby culminating in pancreatic insufficiency. This, in turn, perturbs the synthesis of insulin, a pivotal endocrine hormone responsible for the regulation of glycemic levels. Standardized protocols advocate for the systematic screening of CFRD among all individuals with CF, commencing at the age of 10 years using the oral glucose tolerance test (OGTT). Therapeutic modalities encompass insulin therapy, dietary adjustments, and the vigilant monitoring of glycemic parameters. The overarching objective is to maintain blood glucose levels within a targeted range to mitigate the advent of diabetic complications. Untreated or sub-optimally managed CFRD can precipitate a spectrum of deleterious health ramifications, encompassing cardiovascular afflictions, neuropathy, renal dysfunction, and ocular complications.